Analysis of Effective Principal Leadership Based on Trait Approach in Improving Education Quality - Satyawati, Sophia Tri (Jurnal Paedagogy, 2024)
This research aims to analyze the leadership traits of effective school principals in improving the quality of education. The method used in this research was a mixed method with qualitative and quantitative approaches. The subjects of this research were principals, teachers, and education personnel in Semarang Regency. Data collection techniques used questionnaires and in-depth interviews. Quantitative data were analyzed using percentage and categorical, while qualitative data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing. The results of this study indicated that the personality traits of effective principals in improving the quality of education include: aspects of intelligence in the high category (85%), aspects of self-confidence (85%), persistence (88%), integrity (90%), and agreeableness (94%) included in the very high category. The findings of this study showed that principals’ personality traits could change when dealing with senior teachers when the principal’s tenure is coming to an end, when they are transferred or when they are about to retire.